In vitro models of the blood-brain barrier - Couraud, Pierre-Olivier (Henry Stewart Talks, 2008)
Blood-brain barrier, In vitro models of blood-brain barrier, Blood-brain barrier permeability, Brain endothelium and tight junctions, Transporters at the blood-brain barrier
Archived at 2018/10/28